ROLE PEOPLE ISLAM TO ENFORCEMENT LAW IN INDONESIAN STATE SYSTEM: PERSPECTIVE OF ISLAMIC LEGAL PHILOSOPHY - Abdul Mannang; Aisyah Kara; Abdul Rahman Sakka (PT. Jurnal Center Indonesia Publisher, 2025)
Enforcement law is component important in guard stability system state administration Indonesia Which compound. Muslims, as majority resident Indonesia, own not quite enough answer big in support enforcement law Which fair and ethical. Through the perspective of Islamic legal philosophy, this study explores how Islamic legal principles such as justice ('adalah), welfare (maslahah), and obedience to the law (ta'zim al-qanun) can strengthen the Indonesian legal system. This journal uses a descriptive qualitative research method with a literature review approach to understand the role of Muslims in the context of law enforcement in Indonesia. The findings show that Muslims have a significant role in fighting for the values of justice and maintaining the integrity of the legal system based on Islamic spiritual, moral, and ethical foundations.